USO DA REALIDADE VIRTUAL NO LETRAMENTO EM SAÚDE: UMA REVISÃO SISTEMÁTICA - Galetto Husch, Rodrigo; Antônio Pereira de Castro Junior, Marco; Henrique Alves dos Santos, Pedro; Franco Maciel , Ruberval; Dalla Vechia, Vinicius; José Grande , Antônio (ANAIS DO ENIC, 2026)
-